Socio-economic baseline survey of selected households for Climate-Smart Dairy systems (CSD) in East Africa through improved forages and feeding strategies project - Notenbaert, An Maria Omer; Kihoro, Esther; Osele, Vivien; Nzolega, Beatus; Mukiri, Jessica; Nyakundi, Fridah Nyabate; Crane, Todd A. (Bioversity International and the International Center for Tropical Agriculture, 2020)
IFAD CSD baseline dataset contains detailed information about household composition, production systems and activities, land and labour allocation, income from on-farm and off-farm activities, household consumption of food, and assets, land ownership and allocation of activities, with an emphasis on livestock production activities, livestock feeding strategies, selling of livestock products in the Southern Highlands of Tanzania and Rwanda. (2020-02-10)